IDENTIFICATION OF STUDENT INTEREST IN LEARNING AT SMP N 25 PADANG - Dira Luckya Helmi; Arief Muttaqiin (SEMESTA: Journal of Science Education and Teaching, 2023)
Science learning at this time is one of the lessons that according to some students is classified as fun and there are also some who think science is a difficult lesson. On this basis, this study aims to identify students' interest in learning at SMP N 25 Padang. This research is a descriptive research. The research subjects were class VIII students. The data of this study were obtained through questionnaires distributed to VIII grade students of SMP N 25 Padang. The questionnaire data was analyzed with descriptive statistics. After reviewing several previous studies, it shows that if the learning design is adjusted to students' learning interests, then learning can run optimally. The results of this study show that students prefer the group discussion method in learning. In addition, students also feel more active when given challenging questions. Then, students feel interested in learning science if there are practicum activities (experiments) in it.